LOCH Open Access in REF: Planning Workshop - Update from Heriot-Watt - Kerr, Linda (Heriot-Watt University, 2015)
Presentation by Linda Kerr on Heriot-Watt University's approach to implementing Open Access requirements for the post-2014 REF.
Keywords: REF, open access, open access good practice, Heriot-Watt University, LOCH Jisc